Hungry for the queen: Honeybee nutritional environment affects worker pheromone response in a life stage‐dependent manner. (23rd October 2018) - Walton, Alexander; Dolezal, Adam G.; Bakken, Marit A.; Toth, Amy L.
Abstract : Plain Language Summary Abstract: Animal nutritional state can profoundly affect behaviour, including an individual's tendency to cooperate with others. We investigated how nutritional restriction at different life stages affects cooperative behaviour in a highly social species, Apis mellifera honeybees. We found that nutritional restriction affects a worker's queen pheromone response, a behavioural indicator of investment in group vs. individual reproduction. Nutritional restriction at the larval stage led to reduced ovary size and increased queen pheromone response, whereas nutritional restriction at the adult stage led to reduced lipid stores and reduced queen pheromone response. We argue that these differences depend upon the extent of reproductive plasticity at these life stages and that individual worker honeybees may adjust their behavioural and physiological traits in response to nutritional stress to invest nutritional resources in either their own or their colony's reproduction. These results support the role of nutritional stress in the maintenance of cooperative behaviour, and we suggest that historical nutritional scarcity may be an important contributor to the evolution of extreme forms of cooperation. Aplain language summary is available for this article.